Answer:
The third option listed: ![\sqrt[3]{2x} -6\sqrt[3]{x}\\](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B2x%7D%20-6%5Csqrt%5B3%5D%7Bx%7D%5C%5C)
Step-by-step explanation:
We start by writing all the numerical factors inside the qubic roots in factor form (and if possible with exponent 3 so as to easily identify what can be extracted from the root):
![7\sqrt[3]{2x} -3\sqrt[3]{16x} -3\sqrt[3]{8x} =\\=7\sqrt[3]{2x} -3\sqrt[3]{2^32x} -3\sqrt[3]{2^3x} =\\=7\sqrt[3]{2x} -3*2\sqrt[3]{2x} -3*2\sqrt[3]{x}=\\=7\sqrt[3]{2x} -6\sqrt[3]{2x} -6\sqrt[3]{x}](https://tex.z-dn.net/?f=7%5Csqrt%5B3%5D%7B2x%7D%20%20-3%5Csqrt%5B3%5D%7B16x%7D%20-3%5Csqrt%5B3%5D%7B8x%7D%20%3D%5C%5C%3D7%5Csqrt%5B3%5D%7B2x%7D%20%20-3%5Csqrt%5B3%5D%7B2%5E32x%7D%20-3%5Csqrt%5B3%5D%7B2%5E3x%7D%20%3D%5C%5C%3D7%5Csqrt%5B3%5D%7B2x%7D%20%20-3%2A2%5Csqrt%5B3%5D%7B2x%7D%20-3%2A2%5Csqrt%5B3%5D%7Bx%7D%3D%5C%5C%3D7%5Csqrt%5B3%5D%7B2x%7D%20%20-6%5Csqrt%5B3%5D%7B2x%7D%20-6%5Csqrt%5B3%5D%7Bx%7D)
And now we combine all like terms (notice that the only two terms we can combine are the first two, which contain the exact same radical form:
![7\sqrt[3]{2x} -6\sqrt[3]{2x} -6\sqrt[3]{x}=\\=\sqrt[3]{2x} -6\sqrt[3]{x}](https://tex.z-dn.net/?f=7%5Csqrt%5B3%5D%7B2x%7D%20%20-6%5Csqrt%5B3%5D%7B2x%7D%20-6%5Csqrt%5B3%5D%7Bx%7D%3D%5C%5C%3D%5Csqrt%5B3%5D%7B2x%7D%20-6%5Csqrt%5B3%5D%7Bx%7D)
Therefore this is the simplified radical expression: ![\sqrt[3]{2x} -6\sqrt[3]{x}\\](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B2x%7D%20-6%5Csqrt%5B3%5D%7Bx%7D%5C%5C)
Answer:
136
Step-by-step explanation:
(6-10i)(6+10i)
36 +60i - 60i - 100i²
36 - 100i² (i² = -1)
36 + 100
136
Answer:
(x, y)=(301 43)
( ---- , ---)
( 29 29)
Step-by-step explanation:
The answer is the first one:
bc its not growing by a (-)1/2 and the 3rd one just doesnt make sense
Instead of typing it all on here, I included my explanations with the work.